The limits of gender domination : women, the law, and political crisis in Quito, 1765-1830 - Black, Chad T. (Chad Thomas) (University of New Mexico Press, 2010)
By documenting the progressive removal of limits to patriarchal power in the waning years of the Spanish Empire in Quito, this study traces the genealogy of legal patriarchy in Spanish America.